Thin film material made of resistive alloy and method for manufacturing the same
Patent Information
- Application Number
- JP2026049103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-01
- Filing Date
- 2026-03-24
- Publication Date
- 2026-10-14
Smart Images

Figure 2026167562000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a thin film material made of a resistive alloy, and more particularly to a thin film material made of a resistive alloy using a thin film material of austenitic stainless steel as a starting material. [Background technology]
[0002] The applicant has obtained a patent (Patent No. 7663921) in Japanese Patent Application No. 2024-181790 for a thin film material composed of amorphous and crystalline SUS316 (316L). Since SUS304 (304L), which was not recognized as a patent in Japanese Patent Application No. 2024-181790, exhibits similar functionality, the applicant has filed a new application, Japanese Patent Application No. 2025-60386, and hereby files this domestic priority application, supplementing the shortcomings described in the specification of Japanese Patent Application No. 2025-60386.
[0003] Stainless steel, being an iron-based material, is widely used not only as a structural material but also as a heater material due to its excellent corrosion resistance and heat resistance. As a heater material, it is used as a so-called sheath material, where a heating element is inserted inside a stainless steel tube to protect it, and it is also used as the heater itself because its resistivity is 40 times that of copper.
[0004] Furthermore, martensitic steels (including stainless steel) with a body-centered cubic structure can be sintered (quenched) using the carbon they contain to enhance their corrosion resistance and heat resistance. Steels with such enhanced corrosion and heat resistance can then be used as high-temperature heaters.
[0005] On the other hand, amorphous alloys are increasingly being used as heaters due to their excellent corrosion resistance, heat resistance, and higher resistivity compared to alloys of the same composition. Furthermore, iron-based amorphous alloys exhibit soft magnetism and have been used as magnetic materials, for example, in the magnetic heads of tape recorders.
[0006] One method for producing amorphous alloys is to rapidly cool molten metal. For example, Japanese Patent Publication No. 2020-146714 and Japanese Patent Publication No. 2018-151172 disclose a method in which a container containing metal raw materials is heated by electromagnetic induction to melt them, and the molten metal is applied in a film-like manner to a cooling roll and rapidly cooled. Furthermore, Japanese Patent Publication No. 51-73920 discloses a composition for amorphousizing iron-based materials.
[0007] Furthermore, there is a method of implanting ions of elements such as carbon, phosphorus, and boron into the target object using an ion implantation device. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2020-146714 [Patent Document 2] Japanese Patent Publication No. 2018-151172 [Patent Document 3] Japanese Patent Application Publication No. 51-73920 [Overview of the Initiative] [Problems that the invention aims to solve]
[0009] It is predicted that high thermal efficiency can be obtained by using a strip-shaped heater material to increase the heat dissipation area. Currently, the materials that can be seen on the internet for strip-shaped heater materials include stainless steel, iron, chromium, and aluminum alloy (trade name Kanthal®).
[0010] Since the melting point of stainless steel is 1400-1500°C, it can be used at temperatures of around 1000°C. Therefore, we will consider a heater using a 30μm thick stainless steel strip.
[0011] The resistivity (SUS316L) is 7.7 × 10⁻⁶ as stated in the literature. -7To obtain a stainless steel heater with a resistance of Ωm, a width of 5 mm, a thickness of 30 μm, and a power output of 1 kW (10 Ω) at a voltage of 100 V, a length of material slightly less than 2 m would be required. Considering the temperature dependence of the resistance, the required length could be reduced by 30%, but the need for a long piece of material remains.
[0012] The resistivity of the aforementioned iron, chromium, and aluminum alloy is 14.5 × 10⁻⁶. -7 Since the resistance is Ωm, if the thickness is 30 μm, then about half the length would suffice. However, considering that currently only materials with a thickness of 80 μm or more are commercially available (according to the catalog published by Tokyo Resistance Wire Co., Ltd.), it is thought that it is either not possible to make it thinner, or that making it thinner would cause problems in use.
[0013] Furthermore, considering the specific heat of various heater materials in relation to the present invention, there are various types of stainless steel, but all have a specific heat of 500 J / kg·K. Nichrome has a resistivity of 10.8 × 10 -7 Its Ωm is relatively high, but it is also highly temperature-dependent, and its specific heat is 460 J / kg·K, which is not significantly lower than that of stainless steel.
[0014] Furthermore, the resistivity of the aforementioned iron, chromium, and aluminum alloy is 14.5 × 10 -7 Its high Ωm density, low temperature dependence, and high heat resistance make it useful as a heater, but its specific heat of 420 J / kg·K is not significantly lower than that of stainless steel or nichrome.
[0015] Based on the above, the requirements for a heater material are high resistivity, low temperature dependence of resistivity, and low specific heat, but it is believed that no heater material currently meets all three of these conditions.
[0016] The methods for producing amorphous alloys described in the above patent documents involve melting the material, then rapidly cooling it by extruding it through a rotating cooling drum to form a strip. The temperature drop rate for this "rapid cooling" is described in the literature as 10 2 ℃ / s~10 6A description of a wide range of up to °C / s is recognized, which is presumably different depending on the target substance, but 10 2 It can be said for certain that the rate is not lower than °C / s. The amorphous metal obtained by this method is characterized by high resistivity and soft magnetic properties, but it requires corresponding equipment and results in high costs.
[0017] There is also a method of obtaining amorphous powder by sputtering, but in this case, it is necessary to re-solidify the obtained amorphous powder, and it is technically difficult to obtain a long strip material.
[0018] Furthermore, there is a method of implanting ions of elements such as carbon, phosphorus, and boron into a target object using an ion implanter, but this method can only obtain products of a size limited by the size of the ion implanter described above.
[0019] Meanwhile, Japanese Patent Application No. 2024-181790 discloses a thin film material made of a resistor alloy that forms an amorphous composition from stainless steel material and a method for manufacturing the same, but it was not clear what the peak near 20° in the XRD pattern of stainless steel 304 indicates.
[0020] The present invention has been proposed in view of the above conventional circumstances, and aims to obtain a strip-shaped or wire-shaped heater material that has high resistivity, low temperature dependence of resistivity, low specific heat, high durability and heat resistance, and a length adapted to the situation. [Means for Solving the Problems]
[0021] The present invention is a thin film material with a thickness of 50 μm or less having a metal composition of stainless steel 304 or 3304L, the thin film material being made of a resistor alloy having an amorphous structure and a metal structure mixed with the amorphous structure, which has peaks only at approximately 65°, and between 82° and 83° in the XRD waveform.
[0022] The above thin film material is manufactured by the following procedure.
[0023] Stainless steel 304 or 304L inevitably contains impurities (C, Si, S, P). Focusing on carbon, the process involves removing impurities from molten stainless steel 304 or 304L so that the carbon concentration is 1 / 10 or less of the upper limit of the JIS standard (impurity treatment process). Steel of a predetermined thickness is obtained from the molten metal from which the carbon has been removed (steelmaking process). A thin film material is obtained by cold-rolling the resulting steel to a thickness of 50 μm or less (cold rolling process).
[0024] The surface of the thin film material obtained by cold rolling is polished to create scratches on the surface (polishing step). A sintering agent, which is sodium silicate mixed with carbon powder as a carbon source, is applied to one surface of the thin film material (coating step). The applied sintering agent is wiped off with a blade and the carbon powder is applied (wiping step). The discarded thin film material with the carbon powder fixed is heated to 800-1000°C (heating step). The heated thin film material is rapidly cooled with water (cooling step). [Effects of the Invention]
[0025] This invention provides a thin film material made of an amorphous resistive alloy by processing steel obtained from molten metal that has been reduced in impurity concentration (carbon concentration) through a normal manufacturing process. This thin film material has high resistivity, corrosion resistance, and heat resistance, and because it has a low specific heat, it can be used as a heater material to obtain high temperatures with little energy input. [Brief explanation of the drawing]
[0026] [Figure 1] This is the X-ray diffraction pattern of sample 1 (13 μm). [Figure 2] This is an XPS image of sample 1 (13 μm). [Figure 3] This is the X-ray diffraction pattern of sample 2 (28 μm). [Figure 4] This is the X-ray diffraction pattern of sample 3 (12 μm). [Figure 5] This is the reference pattern for the X-ray diffraction pattern of stainless steel 316 and 316L. [Figure 6]This is the standard pattern for the X-ray diffraction pattern of stainless steel 304. [Figure 7] This diagram shows the temperature measurement process. [Modes for carrying out the invention]
[0027] The present invention uses austenitic stainless steel SUS316L (or 316) as a starting material. Its metal composition, in weight percent, is Cr: 16.00~18.00, Ni: 10.00~15.00, Mo: 2.00~3.00, Mn: ≤2.00, with the remainder being Fe.
[0028] The metallic composition of SUS316L (or 316), specifically Ni, is 10.00-14.00 mass% for SUS316 and 12.00-15.00 mass% for SUS316L. Therefore, 10.00-15.00 mass% was used above.
[0029] Alternatively, SUS304 (or 304L) can be used. Its metal composition, in weight percent, is Cr: 18.00~20.00, Ni: 8.00~10.50 (304L: 9.00~13.00), Mn: ≤2.00, with the remainder being Fe.
[0030] Austenitic stainless steel inevitably contains impurities (C, Si, S, P). While the JIS standard specifies an upper limit of 0.03% by weight for carbon in SUS316L and SUS304L (0.08% by weight for SUS316 and 304), here, steel with carbon removed to a technically feasible level—less than 1 / 10—is used. In the examples below, the carbon content is reduced to approximately 1 / 100.
[0031] To produce steel with the above composition, the molten metal of austenitic stainless steel is treated for impurities. This impurity treatment is a technique commonly used in steelmaking, and is performed by blowing oxygen into the molten metal container (tundish). This causes carbon to turn into carbon dioxide and other substances to turn into oxides, which are removed from the molten metal as slag. This low-carbonization makes it easier for the carbon that will be applied to the surface in the subsequent sintering process to penetrate, facilitating amorphous formation.
[0032] Next, a steel sheet with a thickness of approximately 1 mm is obtained from the molten metal, which has been treated for impurities (low-carbonization), using a conventional method. After curing this steel sheet in a vacuum at a temperature of approximately 1000°C for about an hour, it is cold-rolled to obtain a thin film material with a thickness of 50 μm or less. Cold rolling allows the material to be formed to a uniform thickness, thus ensuring uniformity of properties even in long products.
[0033] To remove oxides and impurities adhering to the surface of the stainless steel thin film material obtained as described above, it is polished with an abrasive roller. Here, polishing means removing a very thin layer of surface deposits and does not mean achieving a mirror finish. Therefore, the important point is that the abrasive roller creates microscopic scratches on both surfaces. Alternatively, microscopic scratches can also be created on both surfaces by using abrasive powder, or by using a manual abrasive scouring pad or abrasive paper.
[0034] A sintering agent, which is sodium silicate (or sodium silicate containing potassium silicate) mixed with carbon powder as a carbon source, is applied to one side of the polished thin film material of a predetermined thickness obtained in this way. After applying the sintering agent, the sodium silicate is wiped off with a rubber blade, so that as a result, the sodium silicate containing carbon powder adheres to the surface of the stainless steel thin film in an extremely thin layer (estimated to be less than 1 μm).
[0035] At this time, as mentioned above, the surface of the thin film material has scratches from polishing, so when wiped with the blade, the carbon powder and the like get embedded in the scratches and become fixed to the surface of the stainless steel.
[0036] As described above, the stainless steel thin film material coated with sintering agent is heated at 800°C to 1000°C for approximately 15 to 25 seconds, and then rapidly cooled with water.
[0037] The thickness of the thin film material described above should preferably be 50 μm or less, as long as the sintering agent is applied to only one side of the thin film material. If the thickness exceeds this, the conversion to amorphous material by sintering, as described below, will not extend to the entire thickness of the object.
[0038] In addition, although boric acid is mixed into the sintering agent in the present invention, this boric acid is added for the purpose of preventing high-temperature cracking of the workpiece and is considered to contribute little to amorphous formation, as will be explained later.
[0039] Commercially available sodium silicate is used as the above-mentioned sodium silicate, and carbon powder and boric acid are added to the sodium silicate in a weight ratio of 8:1:1 to 4:3:3. However, the amount of carbon penetration into the thin film material is correlated with the heating temperature, heating time, and carbon concentration, and the above weight ratio cannot be uniformly determined.
[0040] Japanese Patent Publication No. 51-73920 states that the material conditions for changing an iron-based material into an amorphous material are one or more of carbon, phosphorus, and boron. However, as in the present application, it is thought that carbon is what penetrates into the thin film material by heat after it has been converted to steel.
[0041] In fact, when the applicant measured the concentrations of carbon and boron in the following examples, almost no penetration of boron into the thin film material was observed, suggesting that carbon contributes to amorphous formation. Boron is thought to have a function similar to that of welding agents, preventing high-temperature cracking.
[0042] Furthermore, the sintering agent may be applied to one side of the thin film material or to both sides.
[0043] The temperature during sintering is generally 800°C to 1000°C, which is the temperature range used in conventional iron quenching treatments; this temperature is maintained for 15 to 25 seconds, followed by rapid quenching through immersion in water.
[0044] As a result, carbon rapidly penetrates into the thin film material. The rapid quenching forms an amorphous structure, while a martensite crystal structure is partially formed, yielding a thin film in which both structures coexist.
[0045] In general, when attempting to obtain an amorphous metal by rapidly quenching a molten metal, 10 2 °C / s to 10 6 °C / s of temperature drop rate is required. In the present invention, a steel thin film, rather than a molten metal, is used as the starting raw material. It is considered that amorphization proceeds due to the synergistic effect of an extremely low carbon concentration set in the process before the material becomes steel, and a thickness of 50 μm or less that enables a temperature drop rate inversely proportional to the thickness.
[0046] In the following, Samples 1 to 3 will be described using an example in which a sintering agent obtained by mixing the above carbon powder and boric acid into sodium silicate (with a weight ratio of 6 parts sodium silicate, 2 parts carbon powder, and 2 parts boric acid) is applied to one side, with a sintering temperature of 900°C and a sintering temperature holding time of 20 seconds.
[0047] <Sample 1 (Inventive product of the present application: 13 μm thickness)> First, impurity treatment is performed at the molten metal stage until the carbon content reaches approximately 1 / 100 of the JIS standard upper limit ratio (0.03 wt%) for SUS316L, and steel with a thickness of approximately 1 mm is obtained from the molten metal. This steel is cold-rolled after undergoing the aforementioned curing process in a vacuum to produce an unpolished thin film material with a thickness of 13 μm. Thereafter, the unpolished thin film material is subjected to the aforementioned polishing to obtain a polished thin film material (the thickness before and after polishing and the thickness after polishing are substantially the same). The 13 μm thickness represents the equipment limit of the applicant, and a thinner thickness is also acceptable.
[0048] Separately, a sintering agent is prepared by mixing commercially available sodium silicate with carbon powder and boric acid in the above proportions. When the sintering agent is applied to the surface of the material and wiped off with a blade, a very thin layer of sodium silicate mixed with carbon powder and boric acid adheres to the surface of the stainless steel thin film, and in particular, the carbon powder and boric acid become embedded in the very fine scratches formed during polishing.
[0049] Therefore, it is preferable that the particle size of the carbon powder be as small as possible, for example, nano-order particles.
[0050] The thin film material in this state is heated to 900°C as described above and held at that temperature for 20 seconds. Then, it is rapidly cooled by immersion in water to complete the sintering process. As a result, as explained below, a portion of the austenite structure transforms into an amorphous structure, and the remainder transforms into a martensite crystalline structure.
[0051] Figure 1(a) shows the X-ray diffraction pattern of the side (front) of sample 1 where the sintering agent was applied, and Figure 1(b) shows the X-ray diffraction pattern of the opposite side (back). There are two points to note here. The reference pattern of X-ray diffraction of SUS316L before processing is shown in the top row of Figure 5(b), which will be described later.
[0052] First, as a result of the sintering process described above in the present invention, the curve is broad on both the front and back surfaces at a shallow angle of 2θ of 40° or less. This broad curve suggests the possibility of an amorphous structure (although it could also be a baseline). Characteristics of amorphous materials include (1) high resistivity and (2) high magnetic permeability.
[0053] The resistivity of SUS316L is 7.7 × 10⁻⁶ according to the literature. -7 Where there is Ωm, in sample 1 it is 14.4 × 10 -7The value is Ωm (calculated from the value at 0.5V application in Table 2, which will be explained later), and the requirement of (1) above is met. The applicant does not have equipment to calculate the permeability numerically, but when a permanent magnet is brought near, the unprocessed SUS316L does not react at all, but sample 1 is attracted. Therefore, the requirement of (2) above is also met.
[0054] However, as explained below, as an effect of the sintering, a portion of the austenitic structure (non-magnetic) of the stainless steel in question is transformed into a martensitic structure (magnetic) (see the peaks around 65° and 82° in Figures 1(a) and (b)). Therefore, the high magnetic permeability cannot be attributed solely to amorphous formation.
[0055] Next, peaks can be seen around 65° and 82° in Figures 1(a) and (b) above. On the other hand, Figure 5(a) is an X-ray diffraction pattern that appears depending on the degree of cold rolling of SUS316, and Figure 5(b) is an X-ray diffraction pattern that appears depending on the degree of cold rolling of SUS316L (https: / / tt-tech.jimdo.com, from "Dr.TT's Metal and Material Technology Problem Consultation"). In Figures 5(a) and (b), the peak of martensite is represented by the symbol M, and the peak of austenite is represented by the symbol A. From Figure 5(b), a slight transformation to martensite, which occurs during the 90% rolling process of SUS316L, is visible around 82°. From this, it can be seen that the peaks appearing around 82° in Figures 1(a) and (b) are martensite peaks. From Figure 5(b), the identity of the peaks appearing around 65° in Figures 1(a) and (b) remains unknown.
[0056] Therefore, referring to Figure 5(a), which shows the processing transformation of SUS316, a martensite peak appears around 65°, and it can be understood that the peaks around 65° in Figures 1(a) and (b) are also martensite peaks.
[0057] Next, comparing Figures 1(a) and 1(b) above, the peaks around 65° and 82° on the front side where the sintering agent was applied (Figure 1(a)) are higher than on the back side where the sintering agent was not applied. In other words, the effect of sintering is more pronounced on the front side and decreases as you move towards the back side.
[0058] Figures 2(a) and (b) are XPS images of the front and back of sample 1, which has a thickness of 13 μm. The fact that the carbon peak indicated by the arrow on the front side (Figure 2(a)) is higher than that on the back side (Figure 2(b)) supports the above. It is thought that this carbon penetration greatly contributes to the formation of the amorphous material shown in Figures 1(a) and (b). In other words, if the carbon content is reduced to less than 1 / 10 of the specified amount at the molten stage, it becomes easier for carbon to penetrate the thin film material in the subsequent sintering process, and in combination with the presence of chromium, amorphous material is formed.
[0059] To rapidly cool the molten metal and form an amorphous substance, 10 2 Rapid cooling at a rate of decrease of °C / s or higher is required. Although the present invention starts from a thin film of steel rather than from molten metal, the thinness of the material and the low initial concentration of carbon (conversely, the ease with which carbon in the sintering agent penetrates) are thought to produce an effect equivalent to rapid cooling from molten metal as described above.
[0060] Here, considering that the carbon concentration of sample 1 was measured at 0.013 w% and the boron concentration at 0.0002 w%, it can be understood that carbon is the one contributing to amorphous formation. Since no boron peaks appear in Figures 2(a) and (b), this is consistent with the low measured concentrations mentioned above, and it is thought that boron contributes very little to amorphous formation. Rather, it is thought to have a function similar to that of general welding materials, preventing high-temperature cracking.
[0061] Furthermore, since the subjects in Figures 2(a) and (b) are stainless steel that originally contains Ni and Mo, the peaks for Ni and Mo should be visible, but they are hidden.
[0062] At what point did the above transformation to martensite occur? Considering that the degree of transformation around 82° in Figure 5(b) is smaller than in Figures 1(a) and (b), and that no transformation to martensite is observed around 65°, it appears that some transformation occurs during the rolling process, but the main transformation to martensite is thought to occur during the sintering process, not the rolling process.
[0063] Furthermore, since no transformation to amorphous material can be observed at all in Figures 5(a) and (b), which show the X-ray diffraction patterns at different degrees of rolling, it can be said that the transformation to amorphous material occurs only during the sintering process.
[0064] From Figure 5(a), it can be seen that stainless steel 316 undergoes some transformation to martensite around 65° and 82° during rolling alone, but the clear transformation seen in Figure 1 is not observed. On the other hand, in the present invention, impurities are treated at the molten metal stage, so the carbon concentration of SUS316 and SUS316L, which have almost the same metal composition, can be made the same at the molten metal stage, and the present invention is applicable not only to SUS316L but also to SUS316.
[0065] <Sample 2 (Invention of this application: 28 μm)> Figures 3(a) and (b) show the X-ray diffraction patterns of the front and back surfaces of SUS316L, which was rolled to a thickness of 28 μm and polished after undergoing the same sintering process as described above, following the impurity treatment, steelmaking, and vacuum curing processes as in Sample 1. While the overall surface is weakly broad, peaks of martensitic structure can be seen around 65° and 82°.
[0066] Figure 3(a) is the X-ray diffraction pattern of the side (front) of sample 2 coated with the sintering agent, and Figure 3(b) is the X-ray diffraction pattern of the side (back) not coated with the sintering agent. On both sides, a low, broad curve is observed, with martensite peaks around 65° and 82°. In this case as well, the peaks on the front side are higher. It is unclear from this figure whether the broad curve represents the amorphous phase or the baseline.
[0067] However, as explained below, the resistivity of sample 2 is 14.4 × 10⁻⁶ -7 Given its extremely high Ωm value, it is thought to represent amorphous material. Furthermore, the peaks around 65° and 82° are larger on the front side than on the back side, indicating that the penetration of the sintering agent is more pronounced on the front side.
[0068] <Sample 3 (Product of the present invention: SUS304, 12μm)> Figure 4 shows the X-ray diffraction pattern of the side of a sample (Sample 3) on which the sintering agent was applied. This sample was obtained by treating molten stainless steel 304 with impurities, going through the steelmaking process and curing process in a vacuum, cold rolling it to 12 μm, and then sintering it as described above. Similar to Figure 1, peaks appear around 2θ 65° and 82°, with a broad elevation in the area where 2θ is low.
[0069] Immediately after sintering, a peak that appears to be Si oxide appears around 20° (see Figure 4 in Japanese Patent Publication No. 7663921), but when stabilized by heat treatment at 400-500°C for 10 minutes or more, the peak around 20° disappears as shown in Figure 4.
[0070] Compared to the reference pattern of SUS304 with 90% rolling shown in Figure 6, the peaks around 2θ of 65° and 82° are considered to be martensite peaks. In addition, a broad elevation showing amorphous material can be observed in the region where 2θ is lower than 40° in Figure 4.
[0071] The broadening observed in Figure 4 is considerably smaller than that in Figure 1, and this is also reflected in the experimental results that will be explained later, indicating that the exothermic effect is not as large as that shown for 316L. Even if this portion is not considered to represent amorphous material, sample 3 would still have crystals corresponding only to the two peaks mentioned above.
[0072] <Measurement> (Device) As shown in Figure 7, a strip heater 11 (each of the comparative products below, or each of the samples of the present invention) is wound spirally around a quartz tube 10 with the gaps as small as possible, and the probe 21 of the thermometer 20 is inserted into the quartz tube 10, and the device is assembled so that the tip of the probe is located in the center of the winding width y.
[0073] Using the above apparatus, voltages were applied at 0.5V intervals between the electrodes (90mm) of each comparative product and the present invention, and the voltage, current, and temperature were measured, and the resistance and power were calculated.
[0074] <Measurement result 1> Table 1(a) shows the measured voltage, current, and temperature, as well as the calculated resistance and power, for comparison sample 1a, which was cut from an unprocessed SUS316L with a thickness of 9 μm to a width of 5 mm, with an electrode distance of 90 mm. Table 2 shows the measured voltage, current, and temperature, as well as the calculated resistance and power, for sample 1s, which was cut from the sintered sample 1 (thickness of 13 μm) to a width of 5 mm, with an electrode distance of 90 mm.
[0075] Table 1(b) is presented based on the data in Table 1(a), converted to the same value as sample 1s with a thickness of 13 μm, and designated as comparative product 1b. The conversion from the data for comparative product 1a with a thickness of 9 μm (Table 1(a)) to comparative product 1b with a thickness of 13 μm is calculated as: Current Ia of comparative product 1a × 13 / 9 = Current Ib of comparative product 1b.
[0076] Furthermore, although the thickness increases from 9 μm to 13 μm, and the current increases accordingly, the increased current is responsible for the temperature corresponding to the increased thickness, so the temperature at each voltage remains unchanged between comparative samples 1a and 1b.
[0077] <Sample 1s and comparative products 1a and 1b> Using the resistance value of comparison product 1b at 0.5V (resistance value at a temperature close to room temperature) of 1.07Ω, the resistivity is 7.7 × 10⁻⁶. -7 The result is calculated as Ωm, which closely matches the value in the literature.
[0078] In contrast, the resistance of sample 1s is 2.00Ω (resistivity 14.4 × 10) when using the current value at a voltage of 0.5V. -7 It shows a value of Ωm, which is slightly less than double the value in the literature at near room temperature.
[0079] Next, the resistance values of the unprocessed samples (comparison sample 1a, comparison sample 1b) and sample 1s show only a small temperature dependence. As will be explained later, the resistance of unprocessed SUS304 has a large temperature dependence, but for SUS316L, both processed and unprocessed samples show little temperature dependence of resistance. This is presumed to be due to the addition of Mo.
[0080] Although there is a difference in thickness between 9 μm and 13 μm, we will compare the raw data of comparison product 1a and sample 1s.
[0081] In Table 2, sample 1s achieves 900°C with an input energy of 70W (13V) (more precisely, the input energy per second, where 1W = 1J / s, and the same applies hereafter). In comparison product 1a in Table 1a, a similar input energy is obtained with an applied voltage of 12-12.5V, but only around 850°C is achieved. Also, in Table 2, sample 1s achieves 882°C with an input energy of 60W (12V), but in comparison product 1a in Table 1a, a similar input energy is obtained with an applied voltage between 11.0-11.5V, but only around 800°C is achieved.
[0082] Generally, the relationship between the input energy Q and the temperature K is determined by the heat capacity and specific heat of the substance and is given by equation (1) below.
[0083] Q = mcΔK···(1) m: mass, c: specific heat, ΔK: temperature change The following description assumes that the specific gravity is the same before and after the sintering process.
[0084] Since sample 1s, with a thickness of 13 μm, has a mass m that is more than 40% greater than that of comparative sample 1a, which has a thickness of 9 μm, it can be inferred that the specific heat of sample 1s is more than 40% less than that of comparative sample 1a.
[0085] Next, we compare the value of comparison product 1b in Table 1(b) with the value of sample 1s in Table 2.
[0086] Sample 1s achieves 900°C with an input energy of 70W (13V). For comparison product 1b, a nearly equivalent input energy is between 10.0 and 10.5V, but only around 750°C is achieved. Furthermore, while Sample 1s achieves 882°C with an input energy of 60W (12V), comparison product 1b, with a similar input energy of 9.5V, only achieves a temperature of around 700°C.
[0087] From the above, it can be understood that when sintering is performed as in the present invention, the material transforms into an amorphous structure, improving heat resistance and reducing specific heat compared to the material before processing. Therefore, when the same amount of heat is applied to comparative product 1b and sample 1s, sample 1s will reach a higher temperature.
[0088] <Considerations regarding specific heat> Here, we attempt to calculate the specific heat of sample 1s (target substance) based on comparative sample 1b (reference substance) whose specific heat c0 (= 500 J / kg·s) is known.
[0089] Focusing on the energy input per second and the temperature change at that time, the power W (watts) shown in each table can be used as the input energy Q in equation (1).
[0090] If W0 is the energy input to the reference substance, m0 is the mass of the reference substance, c0 is the specific heat of the reference substance, and ΔT0 is the temperature change of the reference substance, then W1 is the energy input to the target substance, m1 is the mass of the target substance, c1 is the specific heat of the target substance, and ΔT1 is the temperature change of the target substance, then the following applies.
[0091] W0 = m0c0ΔT0···(2) W1 = m1c1ΔT1···(3) Here, assuming m0 = m1 and the temperature change per second is the same ΔT0 = ΔT1, the difference in specific heats c0 and c1 manifests as a difference in the energy W0 and W1 supplied per second. Conversely, if W0 = W1, the difference in specific heats c0 and c1 manifests as a difference in ΔT0 and ΔT1, but since we cannot measure ΔT0 and ΔT1 here, we will consider the former case.
[0092] However, the temperatures before (and after) the change in temperature ΔT0 and ΔT1 must be the same. From equations (2) and (3) above, if we set m0 = m1 and ΔT0 = ΔT1, we obtain the following equation (4).
[0093] W0 / W1=c0 / c1 c1 = c0W1 / W0··(4) In other words, the specific heat c1 of the target substance is obtained by multiplying the specific heat c0 of the reference substance by the ratio W1 / W0 of the energy required to maintain a specific temperature for both substances.
[0094] For sample 1s (target substance), an input energy of 60W (12V) results in a temperature of 882°C. The corresponding input energy for comparative sample 1b (reference substance) is calculated to be 112W, and the specific heat is calculated as 500 × 60 / 112, yielding 267 J / kg·s. Calculating the specific heat for each temperature range from 50°C to 882°C in this manner yielded roughly similar values across the entire range, with an average of 269 J / kg·s.
[0095] In other words, the specific heat of sample 1s was found to be more than 40% lower than that of the unprocessed product (comparison product 1b), which is in good agreement with the inferences made from comparing the mass m of comparison product 1a and sample 1s.
[0096] <Measurement result 2> Table 3 shows the measured values of voltage, current, resistance, and temperature, as well as the calculated values of resistance and power, for comparison sample 2, which was cut from unprocessed SUS316L with a thickness of 28 μm to a width of 5 mm, with an electrode spacing of 90 mm. Table 4 shows the measured values of voltage, current, temperature, resistance, and power, as well as the calculated values of resistance and power, for sample 2s, which was cut from sample 2, which was processed from SUS316L with a thickness of 28 μm to a width of 5 mm, with an electrode distance of 90 mm.
[0097] In this case as well, the resistance of comparison product 2 does not change much regardless of the temperature rise, similar to comparison product 1a.
[0098] Table 4 shows that when 68.32W (12V) was applied to sample 2s, the temperature was 898°C. For comparison product 2, the corresponding applied energy was between 6.5V and 7.0V, resulting in a temperature of only about 729°C. Also, in Table 4, when 52.43W was applied to sample 2s, the temperature was 802°C. For comparison product 2, the corresponding applied energy was between 5.5V and 6.0V, resulting in a temperature of only about 644°C.
[0099] Following the procedure used to determine the specific heat of sample 1s, the specific heat of sample 2s was determined to be 310 J / kg·T, which is slightly higher than that of sample 1s. However, the effect of the present invention, which is a decrease in specific heat, can also be observed in sample 2s.
[0100] <Measurement result 3> Table 5a shows the measured values of current, temperature, resistance, and power in response to changes in applied voltage when comparing a 5mm wide sample of unprocessed SUS304 with a thickness of 9μm, designated as comparative sample 3a, with an electrode spacing of 90mm. Table 6 shows the measured values of resistance and power when comparing a 5mm wide sample of sample 3s, which was sintered using the same method as above, with an electrode spacing of 90mm, and the current, temperature, and resistance in response to changes in applied voltage.
[0101] Table 5b shows the values obtained by converting the data of the 9 μm comparative sample 3a to the 12 μm sample. The conversion from comparative sample 3a to 3b was performed by assuming that the current of comparative sample 3b = the current of comparative sample 3a × 12 / 9, and that the temperatures of comparative sample 3a and comparative sample 3b remained constant at each voltage.
[0102] From the data at 0.5V application in Table 5a, the resistivity of comparative product 3a (3b) is 7.15 × 10⁻⁶. -7 It was calculated as Ωm, and the literature value is 7.2 × 10⁻⁶. -7 The value is close to Ωm. Also, perhaps because comparative product 3a (3b) does not contain Mo, the resistance value, unlike comparative product 1a (1b), exhibits the temperature resistance characteristics of a metal.
[0103] In contrast, the resistivity of sample 3s, as shown in Table 6 when 0.5V is applied, is 18.5 × 10⁻⁶. -7 The calculated resistance is Ωm, which is very high. Furthermore, in sample 3s, the resistance value does not change with increasing temperature, or even decreases.
[0104] Sample 3s (Table 6) obtained 882°C when 84.24W (12V) was applied. When comparative sample 3b was given a similar input energy temperature, only a temperature of approximately 786°C was obtained, as shown in Table 5(b). Also, in Table 6, 819°C was obtained when 71.4W (11V) was applied. When comparative sample 3b was given a similar input energy temperature, only a temperature of approximately 738°C was obtained, as shown in Table 5(b). Therefore, a certain degree of specific heat reduction effect is observed even with SUS304, but not to the same extent as with SUS316L (Sample 1, Sample 2).
[0105] Using the same procedure as for calculating the specific heat of sample 1s, the specific heat of sample 3s is calculated as follows: A value of 390 J / kg·K is obtained. This value is higher than the value obtained for sample 1s (indicating a weaker effect), but lower than that for nichrome, iron, and chromium-aluminum alloys.
[0106] Furthermore, it can be easily inferred from its composition that similar results would naturally be obtained with SUS304L.
[0107] <Metal crystals> In Figures 1, 3, and 4, peaks of metallic crystals are observed only around 65° and 82° of 2θ. The peak around 65° appears to correspond to the 200-face peak of ferrite, and the peak around 82° appears to correspond to the 211-face peak of ferrite. Since the subject is stainless steel and not iron, these are thought to be martensite peaks.
[0108] Furthermore, the fact that only two peaks are present here means that the crystals of each sample (1s, 2s, and 3s) are aligned in two directions, indicating that their intensity is higher than that of the starting material (austenite).
[0109] Furthermore, if the raw material is rapidly cooled from a molten state, the entire material changes to an amorphous state, and the peaks shown in Figures 1 and 3 do not appear. Therefore, the martensite peaks in Figures 1, 3, and 4 indicate that a thin film was formed before morphogenesis, regardless of whether it occurred during the rolling or sintering process. Conversely, if morphogenesis is performed using the ion implantation method, the material will be in a state where amorphous austenite crystals are mixed in, as shown in Figure 5, etc.
[0110] <Recrystallization> Generally, amorphous alloys recrystallize under prolonged high-temperature conditions (for example, Journal of the Japan Institute of Metals, No. 51 (1987), pp. 95-101). However, when samples 1s, 2s, and 3s of the present invention were maintained at 800°C for 10 hours, there was no change in their resistance values, confirming that they had not recrystallized.
[0111] <Thickness and wire weight> From Figures 3(a) and 3(b) above, it can be inferred that a considerable effect can be obtained even with a thickness of around 30 μm, and that as long as the sintering agent is applied to only one side during manufacturing, an effective effect can be obtained even for thin films with a thickness of about 50 μm.
[0112] When sintering agent is applied to both sides, the effect can be expected up to about 100 μm, but considering that the cooling rate slows down as the thickness increases, it is questionable whether the expected results will be obtained.
[0113] Furthermore, as shown in equation (1), the energy required to bring the heater to a specific temperature depends not only on the specific heat c but also on the mass m. Therefore, discussing the magnitude of the specific heat is not very meaningful when the mass can be freely adjusted.
[0114] On the other hand, stainless steel possesses heat resistance and durability to temperatures above 1000°C even at a thickness of around 10 μm, and as mentioned above, not only its specific heat c but also its mass m can be reduced. Moreover, at this thickness range, the types of alloys that can be realized are limited. In reality, as described in the section on conventional technology, the thinnest commercially available iron, chromium, and aluminum alloys are strip materials with a thickness of 80 μm, and the smallest wire materials have a diameter of 1 mm.
[0115] Considering the above, the most important aspect of the present invention is a method (amorphization) for obtaining an alloy that has strength and heat resistance even when its thickness is reduced (diameter is reduced), and also has high resistivity and low specific heat, and the alloy obtained as a result.
[0116] To produce wire, it is sufficient to cut the processed product obtained as a thin film as described above into a wire shape. Alternatively, a wire-shaped processed product can be obtained by applying the sintering agent around an unprocessed wire and sintering it using the procedure described above. Conversely, a block can also be created by stacking multiple thin films after sintering or by winding them in a spiral shape.
[0117] As explained above, the amorphous alloy according to the present invention has high resistivity, low temperature dependence of resistance, and low specific heat. Therefore, when used as a heater, it can achieve a higher temperature than conventional products even when the same mass and the same power are applied.
[0118] Furthermore, the carbon source contained in the sintering agent may be carbon powder or an organic material containing carbon. Although only carbon has been described, phosphorus may be used instead of carbon as a material contained in the sintering agent. While it is permitted that both SUS316 and SUS304 stainless steels contain phosphorus up to an upper limit of 0.045 w%, in this invention, the concentration is reduced to 1 / 10 or less during the impurity treatment process. Since phosphorus is an unavoidable substance in iron, lowering its concentration before it becomes steel makes it easier for it to penetrate the thin film material during the sintering process, similar to carbon. In this case, phosphoric acid is used as the phosphorus source for the sintering agent. This phosphorus source can be used in addition to or in place of the carbon source.
[0119] Furthermore, as mentioned above, in addition to C and P, Si is also present as an impurity in iron. However, despite the sintering agent containing sodium silicate, which is a silicon source, Si does not appear in the XPS image in Figure 2. This is likely because Si is difficult to incorporate into thin film materials.
[0120] Furthermore, the XRD angles described above are somewhat vague, being stated as being "around 65°" and "around 82°". By referring to multiple data, it can be estimated that "around 65°" refers to the angle between 64° and 65°, and "around 82°" refers to the angle between 81° and 82°.
[0121] [Table 1]
[0122] [Table 2]
[0123] [Table 3]
[0124] [Table 4]
[0125] [Table 5]
[0126] [Table 6] [Explanation of Symbols]
[0127] 10 Quartz tube 11 Heater 20 thermometer 21 probes
Claims
1. A thin film material with a metal composition of stainless steel 304 or 304L and a thickness of 50 μm or less, Amorphous tissue and, A metallic crystal structure is found mixed with the amorphous structure, and the surface waveform on XRD shows peaks only around 65° and 82° 2θ, A thin film material made of a resistive alloy characterized by having the following properties.
2. A method for producing the thin film material described in claim 1, A process to remove carbon from molten stainless steel 304 or 304L to a concentration of 1 / 10 or less of the upper limit of the JIS standard, A cold rolling process to obtain a thin film material by cold rolling a steel of a predetermined thickness to 50 μm or less, obtained from molten metal from which the above impurities have been removed, A polishing step in which the surface of the thin film material obtained by the cold rolling is polished to create scratches on the surface, A coating step of applying a sintering agent, which is sodium silicate mixed with carbon powder as a carbon source, to one surface of the thin film material, A wiping step in which the applied sintering agent is wiped off with a blade to fix carbon powder to the scratches, A heating step of heating the thin film material on which the carbon powder is fixed to 800 to 1000°C, A cooling step is performed in which the heated thin film material is rapidly cooled with water. A method for manufacturing a thin film material made of a resistive alloy, characterized by having the following features.
Citation Information
Patent Citations
Kotojiritsuamorufuasugokin
JP1976073920A
Three-dimensional measuring device, three-dimensional measuring method, and program
JP2018151172A
Method of producing amorphous soft-magnetic material
JP2020146714A